Pendampingan Penyusunan Jadwal Kegiatan Harian Integratif Mahasiswa Universitas Darussalam Gontor - Anggara, Deki Ridho Adi; Nuriz, M. Adib Fuadi; Amrullah, Khasib; Khakim, Usmanul; Haryanto, Haryanto (LP2M INSURI Ponorogo, 2023)
The Community Service Program (CSP) aims to assist in preparing an integrative daily schedule for santri students at UNIDA Gontor. In terms of methods, this CSP uses a Participatory Action Research (PAR) approach, which includes; stages of identification, planning, and preparation of program design, implementation, and monitoring and evaluation. This CSP results in forming a design schedule for daily student activities that integrate Islamic boarding schools, Islamization, and language programs. In conclusion, the CSP carried out has succeeded in fulfilling the stated goals and achievements, namely the design of an integrative daily activity schedule for UNIDA Gontor santri students; as an effort to improve student non-academic achievements. This aligns with the vision that UNIDA Gontor wants to achieve, namely a university with a boarding school system, Islamization of knowledge, and mastery of the language of the Qur'an. However, this CSP also has limitations. The results in a design schedule for daily student activities are still in the form of a draft proposal that has yet to become a policy, so follow-up is needed at the future CSP.